(Re-)defining the self – Enhanced posttraumatic growth and event centrality in stroke survivors: A mixed-method approach and control comparison study. (May 2016) - Kuenemund, Anna; Zwick, Sarah; Rief, Winfried; Exner, Cornelia
Growing evidences highlight the co-existence of negative and positive (e.g. posttraumatic growth) identity changes following stroke. Identity changes were assessed by comparing 42 survivors 21 months after stroke and healthy controls. A total of 26 stroke survivors participated in a semi-structured interview. Stroke survivors showed significantly higher posttraumatic growth ( F (1, 75) = 9.79, p = .003) and integrated the critical life event to a higher extent into their identity (event centrality) ( F (1, 74) = 37.54, p < .001). Qualitative analysis revealed increased appreciation of life and more intense/selective relationships as the most common positive changes. Considering positive changes might provide additional perspectives for rehabilitation.